2015
DOI: 10.1111/ecog.01353
|View full text |Cite
|
Sign up to set email alerts
|

Local human impacts decouple natural biophysical relationships on Pacific coral reefs

Abstract: Human impacts can homogenize and simplify ecosystems, favoring communities that are no longer naturally coupled with (or reflective of) the background environmental regimes in which they are found. Such a process of biophysical decoupling has been explored little in the marine environment due to a lack of replication across the intact‐to‐degraded ecosystem spectrum. Coral reefs lacking local human impacts provide critical baseline scenarios in which to explore natural biophysical relationships, and provide a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
145
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(163 citation statements)
references
References 65 publications
(102 reference statements)
13
145
5
Order By: Relevance
“…Even though six of eight locations are from the same regional group (MHI), the intra-group proximity within cluster 2 is relatively low. This finding supports the hypothesis that chronic human impacts probably alter Pacific coral reefs in such a way that they are no longer reflective of the background environments in which they reside [52].…”
Section: (C) Effects Of Island Sizesupporting
confidence: 84%
“…Even though six of eight locations are from the same regional group (MHI), the intra-group proximity within cluster 2 is relatively low. This finding supports the hypothesis that chronic human impacts probably alter Pacific coral reefs in such a way that they are no longer reflective of the background environments in which they reside [52].…”
Section: (C) Effects Of Island Sizesupporting
confidence: 84%
“…Our findings demonstrate the importance of distinguishing between fishing-induced trophic cascades that are solely instigated by the loss of predators rather than broader anthropogenic-induced ecosystem collapse on coral reefs, which is often due to a multitude of factors in addition to fishing pressure. However, given the high variability of environmental and biological factors such as productivity, habitat complexity, and species richness on coral reefs, the detectability of trophic cascades may significantly differ among geographically distinct reef systems (Salomon et al 2010;Edwards et al 2010;Williams et al 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Regional effects may exist due to differences in environmental conditions such as nutrient input and reef geomorphology across the GBR (Hutchings et al 2008) or biophysical factors (i.e. sea surface temperature, wave energy, system productivity; Williams et al 2015a). In a post hoc evaluation of nutrient availability on the reefs included in this study (Online Resource Table S22), we found no difference in nutrient availability among the management zones (ANOVA: F (2,12) = 0.64, p = 0.544) or between the regions (paired two-tailed t test: t = −1.207, df = 12.971, p = 0.249).…”
Section: Discussionmentioning
confidence: 99%
“…In oligotrophic environments, where ecosystems are predominantly based on nutrient-depleted waters, the increase in phytoplankton biomass driven by the IME is critical for coral reef ecosystems (Williams et al, 2015) and fishery productivity but also contributes to carbon vertical flow (Heywood et al, 1996). Finally, such biological enhancement has to be more carefully described and studied in order to be integrated into global biogeochemical models, and hopefully to better predict the evolution of nearshore marine ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In these surface nutrient depleted waters, the biological enrichment reported near many islands, the so-called "Island Mass Effect" (IME; Doty and Oguri, 1956), locally enhances to the productivity and potential fisheries (Gove et al, 2016). By supporting a greater abundance of fish and reef-building organisms 20 in comparison with more oligotrophic waters, the IME-induced nearshore biological enhancement is also critical for coral reef ecosystems development and sustainability (Williams et al, 2015). The IME may result from many processes such as the vertical transport of nutrient-rich water masses (e.g.…”
Section: Introductionmentioning
confidence: 99%